Efeito da intervenção cirúrgica bariátrica sobre o metabolismo lipídico hepático materno de ratas obesas e sua repercussão sobre a prole - Bertasso, Iala Milene (2017)
In the present study, the lipid profile and the gene and protein expression of enzymes involved in hepatic lipid metabolism and its repercussion in males of adult offspring were evaluated in obese rats submitted to Roux - en - Y gastric bypass (RYGB). Wistar rats obese by the cafeteria diet (CAF) were submitted to false operation (CAF SHAM) or to RYGB (CAF RYGB). Five weeks later, they began the mating season. The offspring males (F1) obtained were named according to the procedure performed in their mothers, in CAF SHAM-F1 and CAF RYGB-F1, who received a standard weaning diet at 120 days of age. Lipid profile and hepatic lipid metabolic pathways were verified in the mothers and pups. Mothers submitted to the RYGB presented reduction of body weight, fat pad and dyslipidemia. However, maternal RYGB promoted accumulation of hepatic fat (grade 3 steatosis), a mechanism probably due to the reduction of hepatic lipogenesis and increased β-oxidation in the rats of the CAF RYGB group. CAF RYGB-F1 offspring presented a reduction in body weight, accumulation of fat, serum triglycerides (TG) and hepatic cholesterol (CHOL) at 120 days. The amount of acetyl-CoA carboxylase (ACC) and stearoyl-CoA desaturase-1 (SCD-1) mRNA was lower, whereas the amount of carnitine palmitoyl transferase-1 (CPT-1) mRNA was higher in animals from the CAF RYGB-F1 group, compared to the animals from the CAF SHAM-F1 group. The protein expression of ACC and the microsomal triglyceride transfer protein (MTTP) was higher, whereas the expression of fatty acid synthetase (FASN) and phosphorylated ACC (pACC) was lower in CAF RYGB-F1 group, when compared to the animals of the CAF SHAM-F1 group. RYGB in CAF rats improved obesity after pregnancy and lactation. However, these animals had severe liver damage, which did not affect males of adult offspring, despite changes in lipid metabolic pathways.